2013
DOI: 10.1139/cjfr-2012-0334
|View full text |Cite
|
Sign up to set email alerts
|

On the risk of systematic drift under incoherent hierarchical forest management planning

Abstract: In theory, linkages between hierarchical forest management planning levels ensure coherent disaggregation of long-term wood supply allocation as input for short-term demand-driven harvest planning. In practice, these linkages may be ineffective, and solutions produced may be incoherent in terms of volume and value-creation potential of harvested timber. Systematic incoherence between planned and implemented forest management activities may induce drift of forest system state (i.e., divergence of planned and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…They decompose the problem into convex sub-problems, which also provide a global optimum. The obtained solution shows a low risk of wood supply failure (Paradis et al, 2013 andParadis et al, 2015). In Troncoso et al (2015), a vertical integrated supply chain is presented.…”
Section: Strategic Levelmentioning
confidence: 88%
“…They decompose the problem into convex sub-problems, which also provide a global optimum. The obtained solution shows a low risk of wood supply failure (Paradis et al, 2013 andParadis et al, 2015). In Troncoso et al (2015), a vertical integrated supply chain is presented.…”
Section: Strategic Levelmentioning
confidence: 88%
“…The failure to harvest consistent with the plan will lead to less wood being available over the long term. (see Paradis et al 2013). It is a case of use it or lose it!…”
Section: Dealing With the Dicotomy: Strategic Harvest; Strategic Capamentioning
confidence: 99%
“…The extent of the impact will, however, vary based on the total harvest at the forest level. A number of studies have demonstrated the linkage between harvest levels and AAC (Armstrong 2004;Paradis et al 2013). Altering silvicultural treatment in a cutblock also changes the total volume harvested.…”
Section: R a F Tmentioning
confidence: 99%